The Implication of Sea-level Rise Toward the Small Island Nation of Maldives: Legal Perspective - Hananto, Pulung Widhi Hari; Trihastuti, Nanik; Basir, Salawati Mat; Prananda, Rahandy Rizki; Rizki, Dzulfiki Muhammad (PROGRAM STUDI MAGISTER ILMU HUKUM FAKULTAS HUKUM UNIVERSITAS DIPONEGORO SEMARANG, 2022)
Climate change has always been a major issue and a long discussion in the international community. One of the tangible manifestations of climate change is rising sea levels. Sea level rise also has a significant impact on small island countries or micro-countries which are geographically small and have very low land elevations. The impact of sea level rise will pose a threat that is quite dangerous for the existence of a small island nation like the Maldives. This article applies normative legal research methods using a conceptual approach, cases and regulations. This study aims to examine the implications of sea level rise on the Maldives perspective and provide options in the form of legal construction to solve this problem. This research found that The UNCLOS does not provide explicit reference against the sea-level rise effected by climate change. However, International community have been making progress to address this issue with a numbers of conferences. This study suggest that The Maldives government should have maximized the implementation of its laws and regulation to mitigate air space pollution coming from GHG Emission. The consistency of its implementation is the important key to mitigate the impact of this sea level rises.